Internal hernia through the mesenteric defect in twin pregnancy: a case report and literature review - Lan Wang; Yuchun Zhu; Huayun Tan (Frontiers in Medicine)
BackgroundInternal hernias through mesenteric defects are rare, particularly in the context of twin pregnancies, and can lead to severe complications such as bowel obstruction and strangulation. Early diagnosis is critical, yet challenging, due to the overlapping symptoms with other abdominal conditions and the limited use of advanced imaging during pregnancy.Case descriptionWe present a 33-year-old woman with a twin pregnancy at 33 + 2 weeks of gestation who experienced acute bowel obstruction due to an internal hernia through a congenital mesenteric defect. The patient presented with persistent upper abdominal pain, nausea, and vomiting. Given the advanced stage of pregnancy and the associated risks, a cesarean section was performed, followed by surgical exploration. Approximately one meter of strangulated small intestine was resected, and the mesenteric defect was repaired. Both mother and infants recovered uneventfully.ConclusionThis case highlights the importance of considering internal hernia in the differential diagnosis of acute abdominal pain during pregnancy. Prompt surgical intervention is crucial to prevent maternal and fetal morbidity.